Peningkatan Hasil Belajar Siswa Kelas VI SDN 02 Toyomarto Materi Luas Bangun Datar Gabungan dengan Model Pembelajaran Jigsaw - Hariyanto, Hariyanto (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2018)
The purpose of this research is to know the improvement of the result of the study of the widespread joint building material in the second grade students in SD Negeri 02 Toyomarto Singosari with Jigsaw learning model. The research method using Classroom Action Research with 2 cycles consisting of 4 phases, namely planning, action, observation and reflection. Data collection method used in this research is observation and post test. Data analysis used is descriptive quantitative data analysis obtained from observation result of learning and post test result at every meeting. The result of the analysis shows that learning with Jigsaw learning model can improve the result of the study of the joint wake up area in the students of class VI SDN 02 Toyomarto academic year 2017/2018. The average value of cognitive learning outcomes I (60.82), then the average cognitive learning outcome II (78.9) showed an increase compared to cognitive learning outcomes I. In addition, Jigsaw learning model also improves student activeness. This is indicated by the percentage of active students more on the learning cycle II (31.11%) compared to cycle I (13,%).